Effect of silver nanoparticle on singlet exciton fission in rubrene films. (2nd September 2017) - Yonemura, Hiroaki; Futaoka, Yuko; Taniguchi, Tatsuya; Sakaguchi, Hiroshi; Yamada, Sunao
ABSTRACT: The fluorescence intensity from rubrene (Rub) in Rub-silver nanoparticle (AgNP) composite film was larger than that in Rub film. The enhancement is most likely attributable to large electric fields due to localized surface plasmon resonance of AgNP. The magnitude of the magnetic field effects in the Rub-AgNP composite film was almost same as those in the Rub film. These results indicate that the triplet excited states of Rub due to the singlet exciton fission in the presence of AgNP are generated much more than those in the absence of AgNP.